Impact of Adjustment and Academic Interest of Children of Working Women on their Educational Achievement in Mathematics and Science (Journal of Informatics Education and Research, 2026)
The present research study is based on the descriptive survey method. The main objective of the research was to study the effect of academic interest and adjustment on the academic achievement in mathematics and science subjects of children of working women. A sample of 100 children of working women was selected using purposive sampling, including 50 boys and 50 girls. For data collection, the Math Achievement Test (MAT) developed by Ali Imam and Tahira Khatoon was used for assessing academic achievement in mathematics, and the Science Achievement Test (SAT) developed by Ali Imam, Gyan Pratap Singh, and S.P. Singh was used for assessing academic achievement in science. For collecting data on adjustment, the Adjustment Inventory for School Students (AISS) developed by Dr. A.K.P. Sinha and R.P. Singh was used.  For assessing mathematical interest, the Mathematical Interest Scale developed by U. Tandon and Ashok Pal was used, and for assessing science interest, the Science Interest Test developed by L.N. Dubey and Archna Dubey was used.  Analysis of the data revealed that the t-value between academic interest in mathematics and academic achievement was 2.09, while in science, the t-value was 2.25. The t-value between adjustment and academic achievement in mathematics was 2.33, while the t-value between science and adjustment was 4.03. Therefore, the researcher found a significant effect of academic interest and adjustment on the academic achievement in mathematics and science subjects of children of working women.